2006
DOI: 10.1128/jcm.00333-06
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Early Diagnosis of Tuberculous Meningitis by Different Assays

Abstract: Cerebrospinal fluid (CSF) and peripheral blood (PBL) were sampled multiple times from 25 patients with a clinical diagnosis of tuberculous meningitis (TBM) and 49 controls, including 27 patients with other infectious diseases of the central nervous system and 22 patients with other noninfectious neurological diseases. We used an enzyme-linked immunospot assay (ELISPOT) to detect anti-Mycobacterium bovis BCG antibody-secreting cells in CSF and PBL, PCR to detect a repeated insertion sequence (IS6110) specific f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
32
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 19 publications
(22 reference statements)
1
32
0
Order By: Relevance
“…In a study among patients with a clinical diagnosis of TBM that compared a dot immunobinding assay for an M. tuberculosis-specific 14-kDa protein antigen with PCR to detect IS6110, specific for M. tuberculosis in the CSF, the immunobinding assay was more sensitive than the PCR method (75% versus 40.5%, respectively) (204). Among the advantages of either antibody or antigen detection methods is that these methods are more applicable to laboratories based in the developing world, where the majority of the TBM burden remains, than more costly PCR-based methods (164,204 (146). In at least one study, the use of the MTD test was not helpful in diagnosing tuberculoma (9).…”
Section: Molecular and Biochemical Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…In a study among patients with a clinical diagnosis of TBM that compared a dot immunobinding assay for an M. tuberculosis-specific 14-kDa protein antigen with PCR to detect IS6110, specific for M. tuberculosis in the CSF, the immunobinding assay was more sensitive than the PCR method (75% versus 40.5%, respectively) (204). Among the advantages of either antibody or antigen detection methods is that these methods are more applicable to laboratories based in the developing world, where the majority of the TBM burden remains, than more costly PCR-based methods (164,204 (146). In at least one study, the use of the MTD test was not helpful in diagnosing tuberculoma (9).…”
Section: Molecular and Biochemical Analysismentioning
confidence: 99%
“…These assays have been evaluated specifically in HIV-coinfected patients (59,180) and also as a means to monitor therapy (180,210). While many of those studies demonstrated improved sensitivity over traditional smear and culture methods, several other studies highlighted the low sensitivities associated with these PCR assays (25,68,112,164,206). Looking at the utility of applying PCR assays to the (206).…”
Section: Molecular and Biochemical Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…TB meningitis (TBM) is a common clinical manifestation involving infection of the central nervous system with Mycobacterium tuberculosis. Delay in diagnosis and treatment leads to neurologic handicap and mortality (Quan et al 2006). Usually, TBM diagnosis is made by clinical suspicion associated with cerebrospinal fluid (CSF) biochemical findings and protein concentration measurement is an important tool for early recognition of neurological disease; however, abnormalities may suggest TBM but do not differ significantly from those observed in other types of infectious meningitis (Thompson 1995).…”
mentioning
confidence: 99%